Association between non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio and serum thyroid function measures: Recent Findings from NHANES 2007–2012 and Mendelian randomization - Tan, Mo-Yao; Zhang, Ping; Wu, Shan; Zhu, Si-Xuan; Gao, Ming (Frontiers in Endocrinology, 2025)
ObjectiveThere is limited epidemiological data regarding the association of blood lipids with thyroid hormones. Thus, the present article aims to explore whether there is an association between non-high-density to high-density lipoprotein cholesterol ratio (NHHR) and thyroid hormones.MethodsWe analyzed samples from 3,881 adults aged 20 years and above who took part in the National Health and Nutrition Examination Survey (NHANES) spanning 2007 to 2012. The study tested for thyroid hormones, including total triiodothyronine (TT3), free triiodothyronine (FT3), total thyroxine (TT4), free thyroxine (FT4), as well as thyroid-stimulating hormone (TSH). Survey-weighted linear regression and restricted cubic spline (RCS) models were employed to investigate the relationship between NHHR and thyroid hormones. Subsequently, subgroup analyses were conducted. In Mendelian randomization (MR), the inverse variance weighting method (IVW) is used as the primary analytical approach.ResultsThis study finally comprised 3,881 adults aged 20 years and older. After extensive adjustments for covariables, the regression analysis revealed significant negative associations between NHHR and FT4 (β: -0.11, 95% confidence interval [CI]: -0.18, -0.04), FT4/FT3 (β: -0.06, 95% CI: -0.08, -0.04), and TT4/TT3 (β: -0.001, 95% CI: -0.001, 0.000). Both observational and Mendelian randomization studies suggest that high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and total cholesterol may not significantly influence the risk of hyperthyroidism or hypothyroidism.ConclusionsThe study indicates negative associations between NHHR and FT4, as well as the ratios of FT4/FT3 and TT4/TT3. This suggests that NHHR may reflect changes in thyroid function, highlighting its potential clinical significance in assessing thyroid function and metabolic health.